Kedudukan Perempuan Dalam Saksi Nikah Dan Relevansinya Terhadap Saksi Nikah Perempuan Di Indonesia - Alfi Hasanah; Zulkifli; Jumni Nelli (al-Battar: Jurnal Pamungkas Hukum, 2024)
The issue of marriage witnesses and its relevance to female marriage witnesses is a topic related to Islamic Law and the principles related to marriage. In Islam, marriage witnesses are an important element in the marriage process, and the presence of fair and legal witnesses is a requirement to ensure the validity of the marriage. The aim of this research is to determine the position of women as marriage witnesses and ensure the validity of the marriage and avoid fraud or injustice in the marriage process. In this research the author used a type of library research. The legal sources used are primary data in the form of hadiths regarding marriage witnesses, legislation and compilations of Islamic law, and secondary data in the form of books, journals and so on. The results of this research explain that the position of women in marriage witnesses and their relevance to female marriage witnesses shows that in Islam, there must be two witnesses to a marriage and they must be male. However, there are differences of opinion between some scholars about whether female witnesses are allowed or not. In terms of its application in the Indonesian context, the author is more inclined to agree with Imam al-Syafi'i's opinion which requires male marriage witnesses, because the arguments used in the case of female witnesses are more specific, and also more relevant to society and have been accommodated. in Indonesian laws and regulations such as KHI. However, the author does not rule out the opinion of Imam Abu Hanifah and others who allow female marriage witnesses.